An excess of glycolytic enzymes under glucose‐limited conditions may enable Saccharomyces cerevisiae to adapt to nutrient availability. Issue 24 (4th September 2022) - Grigaitis, Pranas; Teusink, Bas
Abstract : Microorganisms, including the budding yeast Saccharomyces cerevisiae, express glycolytic proteins to a maximal capacity that (largely) exceeds the actual flux through the enzymes, especially at low growth rates. An open question is if this apparent expression level is really an overcapacity, or maintains the (optimal) enzyme capacity needed to carry flux at (very) low substrate availability. Here, we use computational modelling to suggest that yeast maintains a genuine excess of glycolytic enzymes at low specific growth rates. During fast fermentative growth at high glucose levels, the observed expression of the glycolytic enzymes matched the predicted optimal levels. We suggest that the excess glycolytic capacity at low glucose levels is a preparatory strategy in the adaptation to sugar fluctuations in the environment. Abstract : In this study, we use computational modelling to suggest that in yeast Saccharomyces cerevisiae, the expression of glycolytic enzymes at low specific growth rates is genuinely in excess. We propose that excess glycolytic capacity at low glucose levels is a preparatory strategy in the adaptation to sugar fluctuations in the environment.